A comparative study on the determinants of e-Commerce in the Philippines and Singapore - Palanca, Angelo Miguel V.
The E-Commerce, or also known as Electronic Commerce or Digital Commerce, is defined as buying and selling of goods through the means of an online platform that uses the internet, mobile devices, internet browser and other forms of media that can accommodate the main function of E-Commerce. This platform hopes to create a new way for business to take place without the actual physical buying and selling of items as seen in physical stores, malls and other shops present in a country or place. This study aims to draw out the significant determinants of E-Commerce and see its effect on the Transaction Values of E-Commerce in Singapore and the Philippines through focusing on the variables of Internet Accessibility, Technological Availability, Infrastructure, Information and Communications Technology (ICT), E-Finance, and the Variety and Performance of Online Shops. By conducting Multilinear Regression and other statistical tools to further prove the significance of the variables, the researchers are able to recognize the respective variables' effect on E-Commerce Transaction Values. The results obtained show that these variables and their respective sub-variables do affect the overall value of E-Commerce transactions.